Damage characterisation of amine-functionalized MWCNT reinforced carbon/epoxy composites under indentation loading - Shakil, Usaid Ahmed; Mohd Ruzaimi, Mat Rejab; Norazlianie, Sazali; Shukur, Abu Hassan; Mohd Yazid, Yahya; Ma, Quanjin (Elsevier Ltd, 2023)
Damage resistance of carbon fibre reinforced composites is crucial parameter to be considered at both primary selection and in-service maintenance stages. High stiffness of carbon-epoxy system and stacked configuration make it susceptible to impact induced brittle damages. Delamination is one such life-limiting damage modes that can severely inhibit load carrying capacity of laminates. Hence to improve the damage resistance of composites demands tailoring tough microstructure and altering brittle damage modes with ductile ones. This work attempted to design damage resistant carbon composites through modification of epoxy matrix with amine functionalized multi walled carbon nanotubes (NH2-MWCNT). Laminates with different nanotube concentrations (0.3, 0.6, 0.9 and 1.2 wt. %) were fabricated to investigate its influence on load bearing capacity, toughness and damage resistance of fibre reinforced nanocomposites. Generally, peak force, displacement and toughness until maximum force improved at all nanoparticle concentrations. Matrix cracking was suppressed owing to optimum cross-linking of nanoparticle with matrix. External damage area increased with nanoparticle concentration although delaminated area, mapped through c-scan, was suppressed up to 27.73%. A combination of higher degree of interfacial interactions, induced by nanoparticles, and energy absorbing microstructure was concluded to be behind improvement in the damage resistance of composites.